(untitled) (Journal of Engineering, 2024)
The aim of the present work is to study the e possibility of controlling cracking due to differential temperature rise and differential shrinkage between surface and interior of mass concrete is bot climate .The experimental work consisted of meanaring temperature change with time various depths, within en the mass concrete foundation of 850 cubic meters in Measurements of the concrete shrinkage were also taken surface and st shot climate, The current understanding is that at a temperature difference of 20 C between the core of mais concrete and ita marface will cause cracking lo hot climate, higher temperature difference usually develops, and combined with shrinkage may cause development of wide cracks, even whes precautions are taken, nach as using low heat cement, large cament content The above understanding however cement, large maximum size aggregate and low work that conerve may is not applicable in all cases. It has been shown be designed with a tensile strain capacity of much higher than the values usually reported of between 100 a will tolerate In the case a tummperature difference of the present foundation much higher than 20 own in an earlier fup to 480 micro-strain, which is Band 200 micro-strain C without cracking Such concreta design, small maximum size crushed coarse aggregate and relatively low WiC rato such concrete was designed using the ACI method of mis temperature was lowered and plastic shrinkage cracking was p polyethylene sheneta immediately after The placing was prevented by covering concrete with finishing Simultzorous coeurrence of maximum temperature differential and high shrinkage differential was avoided by after casting which, allows high creep continua water curing for 10 days e place. As a result, a to take mum semperature difference of 41 C between the core of the mats concrete and its surface was recorded without cracking However, 3 days afler termination of wales curing the maximum temperature difference decreased to 14 C. This is, combined with the shrinkage differential, lead to formation (not exceeding 0.15 mm) on the durability purposes of small width cracks concrete surface. These cracks were considered to be acceptable for durability puposes.